Benchmarking thermoception in virtual environments to physical environments for understanding human-building interactions. (April 2018) - Ozcelik, Gokce; Becerik-Gerber, Burcin
Abstract: Thermal comfort influences occupant satisfaction, well-being and productivity in built environments. Several decisions during the design stage (e.g., heating, ventilation, air conditioning design, color and placement of furniture, etc.) impact the building occupants' thermoception (i.e., the sense by which animals perceive the temperature of the environment and their body). However, understanding the influence of design decisions on occupant behavior is not always feasible due to the resources needed for creating physical testbeds and the need for controlling several contributing factors to comfort and satisfaction. Virtual environments (environments created with virtual reality technology) are novel venues for studying human behavior. However, in order to use virtual environments in the thermoception domain, validation of these environments as adequate representations of physical environments (built environments) is imperative. As the first step towards this goal, we benchmarked virtual environments to physical environments under different thermal stimuli (i.e., hot and cold indoor air temperature). We identified perceived thermal comfort and satisfaction, perceived indoor air temperature, number and type of interactions as markers for the thermoceptive comparison of virtual and physical offices. We conducted an experiment with 56 participants and pursued a systematic statistical analysis. The results show that virtual environments are adequate representations of physical environments in the thermoception domain, especially for subjective perceived thermal comfort and satisfaction assessment. We also found that the type of first adaptive interactions could be used as the markers of thermoception in virtual environments.